Peningkatan Hasil Belajar Pendidikan Agama Islam Melalui Metode Role Playing - Dahlia, Dahlia; Sudirman, Sudirman (Fakultas Tarbiyah dan Ilmu Keguruan, 2025)
This study aims to (1) identify the learning activities of Islamic Religious Education (PAI) students using the role-playing method in Grade VII of SMP Negeri 1 Ponrang Selatan, Luwu Regency, and (2) determine the improvement in PAI learning outcomes through the application of the role-playing method. The background of this research is the low learning outcomes of students in PAI subjects, which are caused by the monotonous lecture method, resulting in less active students and low learning motivation. This research employed Classroom Action Research (CAR) using Kurt Lewin's model, conducted in two cycles. The research subjects were 27 Grade VII students of SMP Negeri 1 Ponrang Selatan. Data were collected through observation, tests, and documentation. The results showed that students’ learning activity increased from an average of 77% in cycle I to 92% in cycle II (an increase of 16%). The average posttest score increased from 68 (37% mastery) in cycle I to 90 (100% mastery) in cycle II. Therefore, the role-playing method is proven effective in improving students’ activity and learning outcomes in PAI.